INHOUSE TRAINING IMPLEMENTASI PEMBELAJARAN MENDALAM MELALUI KECERDASAN ARTIFISIAL DAN KODING DI SD MUHAMMADIYAH 2 AMBON - Abdurrachman, Ode; Ritiauw, Leonid; Rahaningmas, Rofika Azzahra (German für Gesellschaft (J-Gefüge), 2025)
This inhouse training program aimed to enhance teachers’ competence in implementing deep learning through the integration of artificial intelligence (AI) and coding at SD Muhammadiyah 2 Ambon. Conducted as a community service project, the program engaged 10 elementary teachers (grades V-VI) using a participatory action research (PAR) approach. The training covered: (1) constructivist learning philosophy, (2) basic AI-coding technical skills, (3) project-based thematic module development, and (4) HOTS-oriented microteaching practices. Evaluation results revealed a significant improvement in teacher understanding, from 32% (pretest) to 82% (posttest), with tangible outputs including 5 innovative teaching modules and 15 technology-integrated HOTS assessment tools. Reflective analysis highlighted that learning by doing and collaborative mentoring were key success factors. The program recommends establishing a community of practice to ensure sustainable capacity building.